Interactive external representations for knowledge-building processes and performance in dyads: An experimental study - Magdalena Mateescu; Simone Kauffeld (Computers in Human Behavior Reports)
Digital tools that enable the production and manipulation of interactive external representations (IER) could be vital in strengthening collaboration and boosting performance. This experimental study with 40 participants working in dyads at a Large Interactive Surface examined the effects of IER on the collaborative processes and solution quality. The results show that even minor changes in interactivity can influence both collaborative processes and solution quality. Specifically, higher interactivity led to higher convergence of mental models and solution quality. Additionally, the dyads in the higher interactivity condition tended to focus on different aspects of the problem space, i.e. macro vs. micro-level interaction. Although the level of interactivity did not directly affect conversational turn-taking, the cross-recurrence quantification analysis revealed that it may change dyads' collaborative patterns. High interactive external representations may foster more complex collaboration dynamics with a plurality of patterns. Unexpectedly, turn-taking had no bearing on the solution quality, which is especially surprising considering the results of previous research. The findings contribute to understanding team cognition by taking a nuanced view of digital technology's role in team efficiency and convergence of the mental models. The practical implications of the findings are discussed.